Towards Lattice-Boltzmann modelling of unconfined gas mixing in anaerobic digestion. (15th February 2019) - Dapelo, Davide; Trunk, Robin; Krause, Mathias J.; Bridgeman, John
Highlights: Lattice-Boltzmann (LB) is applied to anaerobic digestion for the first time. Homogenised LB and hybrid bounce-back/free-slip boundary conditions are applied. Lab-scale validation against PIV and radioactive tracer. LB is around 180 times faster than CFD. Abstract: A novel Lattice-Boltzmann model to simulate gas mixing in anaerobic digestion is developed and described. For the first time, Euler–Lagrange multiphase, non-Newtonian and turbulence modelling are applied jontly with a novel hybrid boundary condition. The model is validated in a laboratory-scale framework and flow patterns are assessed through Particle Imaging Velocimetry (PIV) and innovative Positron-Emission Particle Tracking (PEPT). The model is shown to reproduce the experimental flow patterns with fidelity in both qualitative and quantitative terms. The model opens up a new approach to computational modelling of the complex multiphase flow in anaerobic digesters and offers specific advantages, such as computational efficiency, over an analogous Euler-Lagrange finite-volume computational fluid dynamics approach.